The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13154033
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy Prediction Using Differential Evolution Online Sequential Extreme Learning Machine Model

Abstract: Despite increasing energy efficiency requirements, the full potential of energy efficiency is still unlocked; many buildings in the EU tend to consume more energy than predicted. Gathering data and developing models to predict occupants’ behaviour is seen as the next frontier in sustainable design. Measurements in the analysed open-space office showed accordingly 3.5 and 2.7 times lower occupancy compared to the ones given by DesignBuilder’s and EN 16798-1. This proves that proposed occupancy patterns are only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…The study uses data from open-office measurements in Vilnius. As it was already found by the authors in previously published study [15], best correlations in predicting occupancy behaviour are gained based on measured CO2 concentrations. Therefore, presented models are using as input data just PIR (occupancy sensors) and CO2 data.…”
Section: Methods and Methodologymentioning
confidence: 92%
See 4 more Smart Citations
“…The study uses data from open-office measurements in Vilnius. As it was already found by the authors in previously published study [15], best correlations in predicting occupancy behaviour are gained based on measured CO2 concentrations. Therefore, presented models are using as input data just PIR (occupancy sensors) and CO2 data.…”
Section: Methods and Methodologymentioning
confidence: 92%
“…Some monitoring studies showed that average occupancy in offices is just around 60 % [13], [14] and for multi-person offices it is higher and can reach ____________________________________________________________________________ 2021 / 25 527 90 % [14]. Meanwhile Bielskus et al [15] compared measured occupancy with the ones that are used in prediction and found that actual occupancy in an open-office is much lower compared to the DesignBuilder's default values and to the ones provided by EN 16798-1 [16]. These differences are accordingly 3.5 and 2.7 times [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations